Exploring the influence of Instagram on travel destination choice - Tešin, Aleksandra; Pivac, Tatjana; Besermenji, Snežana; Obradović, Sanja (The European Journal of Applied Economics, 2022)
The appearance of social media has brought great changes to the tourism journey. Various such platforms have become an almost inevitable tool in all phases of travel, including organization of travel, during travel, and post-travel. Given the growing popularity of social networks and their widespread use, it is being considered how much they can influence their users. Since Instagram is one of the most widely used social media, the main goal of this research was to find out how much it affects the choice of travel destination. To achieve that, a survey was conducted among 853 participants. The findings showed that Instagram is an important source of information and inspiration in the destination selection process. In addition, it has been found that travel-related content is one of the most followed on Instagram and that it definitely increases the interest of users to visit certain destinations. The paper also discusses the influence of Instagram on the choice of travel destination regarding the certain sociodemographic characteristics of respondents.